Design of a Simple and Cheap Water Electrolyser for the Production of Solar Hydrogen - Ram Prasad (Bulletin of Chemical Reaction Engineering & Catalysis, 2009)
Commercially available conventional alkaline electrolyser and advanced polymer membrane electrolysers for water electrolysis are quite expensive. Taking into account this aspect, a very simple and cheap water electrolyser has been designed and fabricated utilising easily available economical materials for small scale production of hydrogen using renewable energy from photovoltaic panel. The construction details of the electrolyser with a schematic drawing of the experimental set-up for PV production of H2 are given. In order to fabricate the compact electrolyser, two coaxial tubular PVC pipes were used. The lower part of the inner pipe has fine perforations for the transport of ions through electrolyte between the electrodes. Two cylindrical electrodes, cathode and anode are kept in inner and outer pipes respectively. The performance of hydrogen production was measured using a photovoltaic panel directly connected to the electrolyser under atmospheric pressure and in 27wt% KOH solution. Flow rates of hydrogen and oxygen were measured using a digital flow meter. High purity fuel cell grade hydrogen (99.98%) and oxygen (99.85%) have been produced. The experimental results confirm that the present electrolyser has eligible properties for hydrogen production in remote areas. No such electrolyser has been reported prior to this work. © 2009 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)